Creation of a severity index for hidradenitis suppurativa that includes a validated quality‐of‐life measure: the HIDRAscore. (12th May 2020) - Marzano, A.V.; Chiricozzi, A.; Giovanardi, G.; Argenziano, G.; Bettoli, V.; Bianchi, L.; Dapavo, P.; Dini, V.; Fabbrocini, G.; Micali, G.; Offidani, A.M.; Potenza, C.; et al.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, debilitating disease with a considerable effect on patient quality of life. Its clinical severity can be measured using different scoring systems; however, few of them include patient‐centred parameters. Objective: To create a new scoring system for HS that includes a quality‐of‐life instrument, the HIDRAdisk. Methods: This post hoc analysis was carried out within the framework of a multicentre, longitudinal, epidemiologic study conducted over 9 months on quality‐of‐life aspects of HS. The new severity score was created using as reference a question from the Subject Satisfaction Questionnaire (SSQ) concerning the severity of HS as evaluated by the patient. Associated variables were selected using univariable and multivariable logistic regression models. The discriminant capabilities of the final model and of the final score were evaluated by the area under the receiver operating characteristic curve and the Hosmer–Lemeshow test. Results: The study population included 308 patients with HS of any severity grade. According to the results of the regression models, the variables associated with the reference SSQ measure were number of inflammatory nodules, abscesses and draining fistulas; the HIDRAdisk score; and the number of subumbilical lesions. The HIDRAscore is obtained by the sum of the scores associated with the number of these parameters. Possible scores range from 0 to 10. Conclusion: The HIDRAscore is a new scoring system for HS severity which, in addition to the clinical evaluation by the physician, includes a validated patient‐reported outcome measure, the HIDRAdisk.